Corylin increases the sensitivity of hepatocellular carcinoma cells to chemotherapy through long noncoding RNA RAD51-AS1-mediated inhibition of DNA repair - Chen, Chin-Chuan (Cell Death Dis, 2018)
Corylin, a biologically active agent extracted from Psoralea corylifolia L. (Fabaceae), promotes bone differentiation and inhibits inflammation. Currently, few reports have addressed the biological functions that are regulated by corylin, and to date, no studies have investigated its antitumor activity. In this study, we used cell functional assays to analyze the antitumor activity of corylin in hepatocellular carcinoma (HCC). Furthermore, whole-transcriptome assays were performed to identify the downstream genes that were regulated by corylin, and gain-of-function and loss-of-function experiments were conducted to examine the regulatory roles of the above genes. We found that corylin significantly inhibited the proliferation, migration, and invasion of HCC cells and increased the toxic effects of chemotherapeutic agents against HCC cells. These properties were due to the induction of a long noncoding RNA, RAD51-AS1, which bound to RAD51 mRNA, thereby inhibiting RAD51 protein expression, thus inhibiting the DNA damage repair ability of HCC cells. Animal experiments also showed that a combination treatment with corylin significantly increased the inhibitory effects of the chemotherapeutic agent etoposide (VP16) on tumor growth. These findings indicate that corylin has strong potential as an adjuvant drug in HCC treatment and that corylin can strengthen the therapeutic efficacy of chemotherapy and radiotherapy.